G340(P) Alice: atraumatic limp in children presenting to the emergency department. (12th March 2018) - O'Halloran, K; Hurley, S; Okafor, I; Kandamany, N; McNamara, R; Fitzpatrick, P
Abstract : Aims: Atraumatic limp represents a significant proportion of presentations to the ED (1). The majority have self-resolving aetiologies. As part of a quality improvement project, we aimed to reduce unnecessary blood tests, imaging and follow up appointments, by implementing a guideline for the assessment of atraumatic limp. Methods: Following staff education and an awareness campaign, the guideline was implemented and prospectively audited. Data was collected from a clinical report form, and from healthcare records. The analysed data from March to April 2017 was compared to a previous epidemiological study, conducted in the same ED in 2015 (table 1). Results: 35 patients (40% of total) were in a 'low risk group' (ie symptoms<72 hours, afebrile and a normal clinical exam). 14 (40%) of these patients underwent investigations. None of these investigations changed the diagnosis. In total there were 5 changes in diagnosis post discharge. Two were following x-rays reports with abnormalities. Three patients had a diagnosis change that were not initially investigated, one was subsequently diagnosed with HSP after representing with a lower limb non-blanching rash, one represented with ankle cellulitis and one was re-examined and referred to General Paediatrics with increased tone unilaterally. 60% of patients with a diagnosis of transient synovitis (TS) were discharged home without investigation. Of those diagnosed with TS 17% had bloods and 32% had an x-ray. 35% of these investigations were unnecessary according to the guideline. Conclusions: Implementation of a guideline can aid in the assessment of atraumatic limp and reduce the number of investigations and follow up appointments, without significant adverse outcome. Compliance with the guideline can be further improved.